PROJETO ESPAÇO DIGNIDADE E CIDADANIA ADAPTADO PARA ESPAÇO DIGNIDADE EM CASA - Freitas, Ana Cristina Pegoraro de; Teixeira, Isabella Cristina Elias; Silva, Laura Pereira da; Cazassa, Mylady Tatiana Lima; Motai, Ricardo (Sinapse Múltipla, 2020)